Pentecostalism, postmodernism, and reformed epistemology James K. A. Smith and the contours of a postmodern Christian epistemology - Shin, Yoon (Lexington Books, 2022)
"This work critically builds on James K. A. Smith's postmodern Pentecostal epistemology with the aid of Reformed epistemology. The resulting postmodern Christian epistemology retains the central postmodern characteristics of perspectivalism and embodiment while integrating the truth element of Reformed epistemology's warrant criteria"--